PENGARUH RETURN ON EQUITY, CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM - Kadafi, Muhamad; Fuddin, Muhammad Khoirul (Program Studi Ekonomi Pembangunan, 2023)
The share price can be said to be the achievement of the company's success, the strength shown by the existence of market trading transactions in the capital market, the transaction is the result of the observations of investors in the achievements of banking companies in obtaining profits. This study aims to examine the effect of Return On Equity, Current Ratio and Debt to Equity Ratio on stock prices of banking companies listed on the Indonesia Stock Exchange. This research uses quantitative descriptive research, research that uses numbers and is secondary data that has been processed and data obtained directly from the company, research that uses numbers and is secondary data that has been processed and data obtained directly from companies. purposive sampling and resulted in a sample of 39 banks. The results of this study show that simultaneously Return On Equity has a significant negative effect, the current ratio has a significant positive effect, Debt to Equity Ratio has a significant positive effect on stock prices and Return On Equity, current ratio, Debt to Equity Ratio has a significant effect simultaneously.